Ricing Concept According To Islamic Law And Positive Law - Azizah, Nila Nur; Ihsan, Khozin Nur (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Islamic economics has a unique and different value framework compared to conventional economics. In this article we will discuss the concept of price in the context of Islamic teachings. The research method used in this research is a qualitative method in the nature of library research by collecting data from various sources of information, such as books, articles and so on related to the topic of discussion. Prices in Islamic economics are influenced by the principles of justice. Islam teaches the importance of avoiding practices that harm other parties. Therefore prices must be fair and must not create inequality or exploitation. Prices have a significant role in the economy and everyday life and Islam has a specific view on how prices should be set, regulated and run in accordance with sharia principles. In Islam, prices are seen as an important element in economic transactions. Through a better understanding of the concept of prices in Islam, it is hoped that Muslim communities and business people can carry out their economic transactions in accordance with sharia values, create a fairer and more sustainable economy, and contribute to shared prosperity.